2006
DOI: 10.5194/angeo-24-97-2006
|View full text |Cite
|
Sign up to set email alerts
|

Space weather impact on the equatorial and low latitude F-region ionosphere over India

Abstract: Abstract. For a detailed study of the space weather impact on the equatorial and low latitude F-region, the ionospheric response features are analysed during the periods of three recent and most severe magnetic storm events of the present solar cycle which occurred in October and November 2003, and November 2004. The F-layer base height (h'F), peak height (hmF2) and critical frequency (foF2) data, from Trivandrum, an equatorial station and Delhi, a low latitude location, are examined during the three magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Equatorial ionosphere has several characteristic features like the Equatorial Electrojet, Equatorial Sporadic-E, Equatorial Anomaly and Equatorial Spread-F. Therefore, there is a need to study HF frequencies in the equatorial region (Dabas et al 2006;Wichaipanich and Supnithi, 2009;Liu et al 2012) where the diurnal and monthly variations may perform differently in the mid-latitude region. As the equatorial ionosphere has special features, it may consequently pose serious threats to communications and navigation systems compared to the ionosphere over the temperate region Chao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Equatorial ionosphere has several characteristic features like the Equatorial Electrojet, Equatorial Sporadic-E, Equatorial Anomaly and Equatorial Spread-F. Therefore, there is a need to study HF frequencies in the equatorial region (Dabas et al 2006;Wichaipanich and Supnithi, 2009;Liu et al 2012) where the diurnal and monthly variations may perform differently in the mid-latitude region. As the equatorial ionosphere has special features, it may consequently pose serious threats to communications and navigation systems compared to the ionosphere over the temperate region Chao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Significant changes in TEC have also been observed following interplanetary events that are generally attributed to intense disturbance-related electric fields resulting from the magnetosphere-ionosphere interaction processes. The electric fields during geomagnetic disturbances at low latitudes have been attributed to prompt penetration zonal electric fields (Abdu et al, 1995;Sastri et al, 2002;Dabas et al, 2006) and/or delayed disturbance dynamo electric fields (Blanc and Richmond, 1980;Fejer and Scherliess, 1997;Richmond and Lu, 2000;Sobral et al, 2001). It has been shown that these electric fields, depending on their polarity and duration, could produce very significant enhancements or decreases of the vertical TEC.…”
Section: Introductionmentioning
confidence: 99%
“…Dmitriev (dalex@jupiter.ss.ncu.edu.tw) enhancements of ion and electron density (storm-enhanced density or SED) and temperature at the low-and mid-latitude topside ionosphere are detected by means of in-situ space experiments (e.g. Mannucci et al, 2005;Oyama et al, 2005;Yizengaw et al, 2005) and of remote techniques, such as ionosonde, radar and total electron content (TEC) obtained from GPS signal processing (Tsurutani et al, 2004;Yizengaw et al, 2005;Zhao, et al, 2005;Dabas et al, 2006;Becker-Guedes et al, 2007;Huang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%